A case of ganglioneuroma - Özoran, Yavuz; Ruacan, Şevket; Komşuoğlu, Sezer Ş.; Özoran, Afet; Aktürk, Fadıl (The Turkish Journal of Pediatrics, 1987)
The case of an isolated ganglioneuroma localized to the cervical region in an eight-year-old girl is presented. The rarity of this disease in the absence of associated systemic and neuroendocrinological abnormalities is discussed.